Characteristics of NaCI-salinized cucurbits and impact of silicon in alleviating salt stress - Othman Ghani, Muhammad Najib (2017)
Members of Cucurbitaceae are salt-sensitive plants and continuous fertilizer application without sufficient leaching may create saline environment that consequently reducing their growth and yield. Among other methods, silicon fertilization was reported to have some ability to reduce negative salinity effects on many plant species. This study was carried out to evaluate the physiological responses of four selected Cucurbitaceae to salinity stress, and to investigate the possible role of silicon in alleviating salinity effects on the crops. Four types of Cucurbitaceae viz. cucumber (Cucumis sativa), pumpkin (Cucurbita moschata), bitter gourd (Momordica charantia) and bottle gourd (Lagenaria siceraria) were subjected to four levels of NaCl (0, 25, 50, 75 mM) and data at vegetative stages; growth, leaf relative water content (RWC), mineral content in leaf, stem, root, relative chlorophyll content and proline concentration were collected. In the second experiment, a study involving two species of Cucurbitaceae that have shown highest (bitter gourd) and lowest (cucumber) salinity tolerant were performed. The species were subjected to two levels of NaCl (0, 50 mM) and three silicon concentrations (0, 50, 100 mg/L sodium silicate) and data on growth, leaf RWC, leaf mineral content, net photosynthesis and stomatal conductance at vegetative stage were collected. Among all species, bitter gourd was least salt-sensitive while cucumber was most salt-sensitive. In terms of growth, bitter gourd had the lowest reduction of leaf area, plant height and stem dry weight while cucumber had the highest reduction of leaf area. Total reduction of plant dry matter as salinity increased to 75 mM NaCl was the least in bitter gourd, 44.40% and the highest in cucumber, 67.84%. Significant reduction of chlorophyll content was recorded at 75 mM in cucumber and pumpkin while in other species shown no significant reduction. At 75 mM NaCl, cucumber leaf water status was significantly impaired by salinity which marked by highest accumulation of proline (3.55 times compared to control) and strong negative correlation between proline and RWC (r= - 0.83, p ≤ 0.01), whereas in other species no significant association was recorded. When treated with 100 mg/L silicon, growth of salt-stressed and non-salt stressed plants for both species was significantly improved, with more beneficial effects recorded on the salt-stressed plants and salt-sensitive species. In terms of Na+ ion, plants treated with 50 mg/L silicon had 11.11% significantly lower Na+ ion in leaf compared to 0 mg/L silicon, regardless of species and salinity condition. Moreover, treatment of 100 mg/L silicon significantly increased net photosynthesis and stomatal conductance by 12.13 and 30.14% respectively, compared to 0 mg/L silicon treatment. Besides that, plants supplied with silicon at 100 mg/L also had significantly higher RWC compared to non-silicon supplied plants. In conclusion, based on reduction in plant dry matter, accumulation of Na+ and Cl- ions in leaf, degradation of chlorophyll content and impaired leaf water status, bitter gourd exhibited a better adaptation to salinity stress than other Cucurbitaceae tested and application of silicon can alleviate salinity stress in both on salt-sensitive species (cucumber) and on a less salt-sensitive species (bitter gourd) by reducing sodium toxicity, increasing photosynthetic activity and improving leaf water status.